(untitled) (Revista Iberoamericana de Bioética, 2025)
Terminally ill patients experience conditions of life that can become unbearable resulting in the wish to end their life prematurely. One way to end one’s life prematurely is by voluntary stopping of eating and drinking, however this can also be considered a way of refusing food and water like refusal of artificial nutrition and hydration.